Blood and beyond: Properties of circulating and tissue‐resident human virus‐specific αβ CD8+ T cells. Issue 4 (19th February 2014) - van, Michiel C.; Remmerswaal, Ester B. M.; ten, Ineke J. M.; van, René A. W.
<x xml:space="preserve">Abstract</x> CD8+ αβ T‐cell responses form an essential line of defence against viral infections. An important part of the mechanisms that control the generation and maintenance of these responses have been elucidated in experimental mouse models. In recent years it has become clear that CD8+ T‐cell responses in humans not only show similarities, but also display differences to those occurring in mice. Furthermore, while several viral infections occur primarily in specialised organ systems, for obvious reasons, most human CD8+ T‐cell investigations were performed on cells deriving from the circulation. Indeed, several lines of evidence now point to essential functional differences between virus‐specific CD8+ memory T cells found in the circulation and those providing protection in organ systems, such as the lungs. In this review, we will focus on summarising recent insights into human CD8+ T‐cell differentiation in response to several viruses and emphasise that for a complete understanding of anti‐viral immunity, it is pivotal to scrutinise such responses in both blood and tissue.